2022
DOI: 10.1111/jonm.13893
|View full text |Cite
|
Sign up to set email alerts
|

Work readiness of newly graduated nurses transitioning to practice in Saudi Arabia: A cross‐sectional study

Abstract: Aims To explore work readiness among newly graduated nurses transitioning to practice in Saudi Arabia. Background Many challenges encounter newly graduated nurses when transitioning to practice. Higher work readiness has been associated with smooth transitioning to practice. However, little is known about work readiness among newly graduated nurses in Saudi Arabia. Methods Cross‐sectional convenience sample of 174 participants. Results The mean score in work readiness was 338.8 (SD = 69.6). Weekly working hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…According to our results, although clinical practicum duration cannot be considered to have had a direct impact on perceived professional preparedness, a duration of less than 8 hours per day was still a predictor of poor preparedness. This aligns with the research by Monir Almotairy [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our results, although clinical practicum duration cannot be considered to have had a direct impact on perceived professional preparedness, a duration of less than 8 hours per day was still a predictor of poor preparedness. This aligns with the research by Monir Almotairy [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Results from such analysis may help nursing educators tailor interventions to support nursing students in the future. Additionally, we explore the influence of senior nursing students’ demographics on their profiles, Prior research has shown that factors such as part-time experience, relationship with classmates, feeling a sense of belonging at a hospital, average clinical practicum hours per day, voluntary choice of nursing major and feeling nobility toward nursing due to COVID-19 could affect professional preparedness [ 15 – 18 , 20 – 22 ]. In China, nursing students are required to complete an eight-month clinical practicum in general hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, students scored relatively high on overall work readiness and its subscales pre- and post-intervention. Prior research has consistently reported lower levels of work readiness among newly graduated nurses in various countries, including Saudi Arabia [ 17 ], China [ 35 ], and Australia [ 23 ]. However, the level of work readiness was higher among the same group in the United States [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the improved scores on the work competence and social intelligence subscales can be attributed to the intervention, which included comprehensive case studies representing real-life situations faced by practicing nurses, possibly increasing senior nursing students' sense of confidence related to perceived work competence and social skills. A previous study among newly graduated Saudi nursing interns reported that those who began training had higher perceptions of work competence and social intelligence than those who did not [ 17 ]. This suggests that the intervention engaged students in activities that were comparable to the real work environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation